2017
DOI: 10.1042/bcj20161069
|View full text |Cite
|
Sign up to set email alerts
|

The biochemical properties of the twoArabidopsis thalianaisochorismate synthases

Abstract: The important plant hormone salicylic acid (SA; 2-hydroxybenzoic acid) regulates several key plant responses including, most notably, defence against pathogens. A key enzyme for SA biosynthesis is isochorismate synthase (ICS), which converts chorismate into isochorismate, and for which there are two genes in Arabidopsis thaliana. One (AtICS1) has been shown to be required for increased SA biosynthesis in response to pathogens and its expression can be stimulated throughout the leaf by virus infection and exoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…We examined the responses of ips3 plants to virulent Pst and found that they were significantly more susceptible to the bacterial pathogen than transformation control plants (Figure ). The susceptibility of ips3 to Pst was similar to that of ips2 , previously shown to be hypersusceptible to Pst (Murphy et al ., ), and the sid2 mutant (Wildermuth et al ., ; Macaulay et al ., ), which is impaired in salicylic acid (SA) biosynthesis and highly susceptible to pathogen attack (Figure ). As would be anticipated, plants carrying both the ips2 and ips3 mutations showed increased susceptibility to virulent Pst (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined the responses of ips3 plants to virulent Pst and found that they were significantly more susceptible to the bacterial pathogen than transformation control plants (Figure ). The susceptibility of ips3 to Pst was similar to that of ips2 , previously shown to be hypersusceptible to Pst (Murphy et al ., ), and the sid2 mutant (Wildermuth et al ., ; Macaulay et al ., ), which is impaired in salicylic acid (SA) biosynthesis and highly susceptible to pathogen attack (Figure ). As would be anticipated, plants carrying both the ips2 and ips3 mutations showed increased susceptibility to virulent Pst (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Hydathodes are open pores on the leaf margin that provide an entry point for bacterial pathogens such as Pst into the apoplast (Rufián et al, 2018). Elevated levels of defence-related gene expression in cells surrounding hydathodes has been previously reported indicating a role of localized constitutive defence around these vulnerable openings (Macaulay et al, 2017;van den Burg et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we analyzed isochorismate synthase 1 (ICS1; ) for SA, OPDA reductase (OPR3; (Stintzi and Browse, 2000)) and jasmonate resistance 1 (JAR1; (Staswick and Tiryaki, 2004)) for JA, and S-alkyl thiohydroximate lyase (SUR1; (Mikkelsen et al, 2004)) and cytochrome P450 monooxygenase CYP83B1 (SUR2; (Bak et al, 2001)) for GSL. For the SA biosynthetic enzyme ICS1, reverse BLASTs returning A. thaliana ICS1 and isochorismate synthase 2 (ICS2; a functionally redundant enzyme (Macaulay et al, 2017)) were considered best reciprocal BLASTs. The analysis predicts that SA and JA pathways are highly conserved throughout the plant kingdom, while the GSL pathway is only conserved within the Brassicaceae.…”
Section: Figure 1 Evidence Of Nhp Production Across the Plant Phylogmentioning
confidence: 99%
“…For example, the tertiary structures of EntC and MenF have been determined, and many amino acid residues essential or important for ICS activity have been identified [ 22 , 23 ]. In contrast, reports on the biochemical analysis of plant ICSs are limited to that of Catharanthus roseus (CrICS) purified from elicited cell cultures [ 24 ], and those of AtICS1 and AtICS2 expressed in E. coli showed very similar catalytic characteristics [ 25 , 26 ]. In the present study, we analyzed and compared the biochemical properties of AtICS1, NtICS, NbICS, and OsICS expressed in E. coli and N. benthamiana leaves.…”
Section: Introductionmentioning
confidence: 99%